1998
DOI: 10.1088/0953-4075/31/20/002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the electron affinity of lanthanum

Abstract: The electron affinity of lanthanum has been measured using laser photoelectron energy spectroscopy. This is the first electron affinity measurement for lanthanum and one of the first measurements of an electron affinity of a rare-earth series element. The electron affinity of lanthanum was measured to be 0.47 ± 0.02 eV. At least one bound excited state of La − was also observed in the photoelectron spectra, and the binding energy relative to the ground state of lanthanum was measured as 0.17 ± 0.02 eV. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 15 publications
13
39
0
Order By: Relevance
“…For the complicated La, Pt and Au atoms the obtained EA values were in outstanding agreement with the available measurements [14][15][16][17][18][19][20]. However, the DFT calculated EAs for Au and Pt atoms [4] tended to underestimate the measured values.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…For the complicated La, Pt and Au atoms the obtained EA values were in outstanding agreement with the available measurements [14][15][16][17][18][19][20]. However, the DFT calculated EAs for Au and Pt atoms [4] tended to underestimate the measured values.…”
Section: Introductionsupporting
confidence: 79%
“…For Pt the calculated EA value [21] overestimated the measurement by approximately a factor of two. The measured BE for the excited state of the La negative ion [14] agreed moderately with the theoretical value of [22], while for Hf recent calculations obtained very good agreement with each other on the BE [22,23]. Also, recent investigations of near-threshold electron elastic scattering by Hf, Ru and Y revealed neither negative nor zero EAs for these atoms [22].…”
Section: Introductionsupporting
confidence: 70%
“…The two exceptions are La − and Ce − [4], each of which have several potential candidates for E1 transitions that lie >0.3 eV above the anion ground state. These opposite-parity excited states are also predicted by other computationalists using density-functional theory in the La − case [6] and multireference configuration-interaction methodology in the Ce − case [7], and while laser photodetachment electron spectroscopy experiments [8,9] designed to measure electron affinities have not definitively measured these states, it has been suggested that some features in the spectra [4,[8][9][10] correspond to photodetachments from them.…”
Section: Introductionmentioning
confidence: 57%
“…Ground state atoms with low EA values are also required for the quenching of Rydberg atoms through collisions [33]. For the 5d transition metal atoms the binding energy measurement [34] is to our knowledge the only one available for the excited state of La À .…”
Section: Introductionmentioning
confidence: 99%